2019
DOI: 10.4102/sajhrm.v17i0.1188
|View full text |Cite
|
Sign up to set email alerts
|

Personality and job engagement among municipal workers in the Eastern Cape province, South Africa

Abstract: Orientation: Although researchers have discovered many of the beneficial and positive consequences of job engagement, little is known about the multitude of antecedent factors that lead to employee engagement such as personality.Research purpose: The aim of the study was to investigate the relationship between the big five personality traits and job engagement among municipal workers.Motivation for the study: The motivation of this study is to examine the relationship between personality and psychological cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Efficient service delivery in stressful public sector environments depends on employee performance (Mhlanga et al, 2019). Van de Walle et al (2015) found that opportunities to help others and contribute to society draw individuals into public service.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient service delivery in stressful public sector environments depends on employee performance (Mhlanga et al, 2019). Van de Walle et al (2015) found that opportunities to help others and contribute to society draw individuals into public service.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient service delivery in stressful public sector environments depends on employee performance (Mhlanga et al., 2019). Van de Walle et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although agreeableness had scored as poor on the reliability test while having a weak statistically significant relationship with affective commitment, it was the only predictor, alongside Conscientiousness, that had a moderately significant relationship with employee engagement. It was concluded in a study (Shaban, 2018) that agreeableness and openness to experience were found out to be significant, while in another study (Mhlanga et al, 2019), agreeableness, together with Conscientiousness and openness to experience, represented the most variance. Additionally, in another study (Shukla, Aggarwal, Adhikari, & Singh, 2014), it was found that Conscientiousness, agreeableness, and openness to experience had a moderately significant relationship, whereas extraversion and neuroticism had a weak and significant relationship.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, the hypotheses and sub-hypotheses were firstly tested with Pearson's r (Ashton & Lee, 2009;Yamagata et al, 2006) to investigate whether there is a correlation between the variables. Afterward, to determine the relationship between the hypotheses, linear regressions (Mhlanga, Mjoli, & Chamisa, 2019;Sev, 2019;Shaban, 2018) were used as shown in Table 3 and Table 4 below…”
Section: Neuroticismmentioning
confidence: 99%
“…In our opinion, this statement is also very relevant for municipal employees of rural areas, who in their professional practices are faced with complex socio-economic issues: environmental management, a lower standard of living in comparison with the city, the availability of high-quality services in education, medicine, culture, social and psychological stress and dissatisfaction of the rural population with life. To overcome these situations, leaders are needed with certain personal qualities and a high level of labor motivation [4] and capable of involving the local community in positive transformations [5,6,7]. The authors of Gyensare M. A., Kumedzro L. E., Sanda, A., Boso N. also speak about the relevance of this approach in their article [8].…”
Section: Introductionmentioning
confidence: 99%